Characterization and Evaluation of Semi-IPN Hydrogels Consisted of Pectin and Poly(acrylonitrile) for Drug Delivery Systems - Sadeghi, Mohammad; Gudarzi, Anahita; Safari, Soudeh; Shahsavari, Hadis; Sadeghi, Hossein (Asian Journal of Chemistry, 2013)
In the present paper, attention is paid to synthesis and evolution swelling behaviour of a superabsorbent hydrogel based on pectin (Pec) and polyacrylonitrile (PAN) carriers for the controlled delivery of ephedrine. The physical mixture of pectin and polyacrylonitrile was hydrolyzed by NaOH solution to yield pectin-poly(sodium acrylate-co-acrylamide) superabsorbent hydrogel. A proposed mechanism for hydrogel formation was suggested and the structure of the product was established using FTIR and SEM spectroscopies, respectively. The pectin-poly(sodium acrylate-co-acrylamide) hydrogel exhibited a pH-responsiveness character so that a swelling-deswelling pulsatile behaviour was recorded at pHs 1.6 and 7.4. In addition, the delivery behaviour of ephedrine from the hydrogel bead was studied. The amount of ephedrine released from the hydrogel bead at pH 1.6 was relatively low (15 %), while this value approached 87 % at pH 7.4. The results clearly suggested that the pectin-bsaed hydrogel may be a potential polymeric carrier for drug delivery in the intestinal tract.